The new Roget's Thesaurus of the English language in dictionary form - Lewis, Norman; Mawson, C. O. Sylvester (Garden City, New York : Garden City Books, 1961)
This dictionary has all entries listed in alphabetical order and in one vocabulary. Synonyms, grouped according to meaning, immediately follow each entry, so that reference to other parts of the book is not absolutely essential. The reconstructed Roget categories are incorporated in the general alphabet etc.
"Based on C. O. Sylvester Mawson's alphabetical arrangement of the famous Roget system of word classification."
ne 26/08/2021
Ref.
Keywords: English language